A Method of Calculating the Depth of Cut in A Lathe After Rolling on A Rough Part. - Valixonov Dostonbek Azim o’g’li; Ohunjonov Zuxriddin Nosirjonovich (Genius Journals, 2022)
In this work, considering the treatment of the cutting tool as another manifestation of the process of decay in hard polymeric materials, a new solution to the problem of improving the quality of the machined surface by the method of initial rolling of the rough part on the basis of the thermofluctuation theory of decay is shown. the polymer sketch detail to be machined is first processed by the initial rolling method
Keywords: Cutter; scraper; tumor; bench